THE EFFECTIVENESS of RAM to HELP THE STUDENTS with HEARING IMPAIRMENT to MAKE SEQUIN EMBROIDERY - Yana Fitriani (Universitas Negeri Padang, 2015)
Abstrack: This research was conducted as a student with totally hearing impairment got obstacles to make sequin embroidery. He could get the thread into the needle hole, sewed straightly with the help of the line, and cut the thread. But he had not been able yet to tie the ends of the thread, sewed straightly without a pattern and without the help of sequins, sewed an archway with pattern and without patterns, sewed archway with the help of sequins and without sequins, smoothed the stitching, tied the ends of the thread after stitching is complete, and the results are not neat. This was a single subject research which used A-B-A design. The baseline condition (A1) was the student’s previously ability in making sequin embroidery. This session consisted of seven observations. In the intervention condition (B), a treatment through which a ram was used, thirteen observations were done and the data was 100%. In the baseline condition (A2), the treatment was no longer given. This session consisted of sixteen observations and the data was 100%. The result of data analysis in and inter-condition showed that the estimation of way tendency, the stability tendency, data record, and the level of changes improved positively. The number of the data overlapped was 7,7%. Hence, it was concluded that the use of ram was effective to help the student with hearing impairment in making sequin embroidery. It was suggested to the school to apply this media to make useful for hearing impairment students. Kata kunci: Keterampilan Sulam Payet, Ram, Anak Tunarungu.